2015
DOI: 10.1063/1.4913598
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study on the effect of SiO2 layers during oxidation of 4H-SiC

Abstract: The effect of SiO2 layers during the thermal oxidation of a 4H-SiC(0001) substrate is examined by performing the first-principles total-energy calculations. Although it is expected that a CO molecule is the most preferable product during the oxidation, CO2 molecules are mainly emitted from the SiC surface at the initial stage of the oxidation. As the oxidation proceeds, CO2 emission becomes less favorable and CO molecules are emitted from the interface. We conclude that the interface stress due to the lattice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 25 publications
(23 reference statements)
2
25
1
Order By: Relevance
“…It is interesting to consider the influence of O defects, which are introduced during thermal oxidation, since they exist within or just below the first SiC bilayer; the region where the interface types differ. We focus on the most stable defects identified in our previous study 6 for each stage of one oxidation cycle. Structures for each are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is interesting to consider the influence of O defects, which are introduced during thermal oxidation, since they exist within or just below the first SiC bilayer; the region where the interface types differ. We focus on the most stable defects identified in our previous study 6 for each stage of one oxidation cycle. Structures for each are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical studies report that C and O-related defects 15 are created during the thermal oxidation process. 3,4,6 Of these, the density of C-related defects is measurable since they generate gap states. Recent experimental studies have reported that the density of defects which generate these states is less than 10 −12 cm −2 eV −1 .…”
Section: Itmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the oxidation of Si 3 N 4 usually happens under high‐temperature conditions (>1000 K), oxygen has sufficient energy to dissociate near the surface of Si 3 N 4 . Therefore, we simulate the oxidation of Si 3 N 4 surface using O atom as an adsorption unit instead of the O 2 molecule, which is also employed in many literatures . Besides, the dissociation energy is very small (0.189 eV), indicating it has little influence on the adsorption energy.…”
Section: Resultsmentioning
confidence: 99%
“…which is also employed in many literatures. [35][36][37] Besides, the dissociation energy is very small (0.189 eV), indicating it has little influence on the adsorption energy. What's more, E nO is half of the energy of an isolated O 2 molecule, so the dissociation energy has been included in the formula of adsorption energy, excluding the error form the ignorance of dissociation energy.…”
Section: Resultsmentioning
confidence: 99%